A Study on The Factors That Affect Employees’ Performance in the Banking Sector in Malacca, Malaysia - Zainisham, Nurhudatul Haziqah; Zaman, Maliza Delima Kamarul (Advances in Social Sciences Research Journal, 2024)
Employees’ performance is the main issue in the current situation especially since Covid-19. Covid-19 has compelled every sector of society to adopt technology and banking sector was no exception. This means employees must be able to use technology to work from office or home as the new norm. Better performance can only be accomplished when employees use their individual talents to boost the organization's performance. This is because employees’ performance is crucial to organizations in the twenty-first century. It enables the organizations to compete advantageously with other businesses in the ever-changing environment. Therefore, this study will be carried out to examine the relationship between motivation, job design, management style, working conditions, workplace reward and training development on employees’ performance. Stratified random sampling will be employed in this study with the respondents of employees from selected banks in Hang Tuah Jaya, Malacca. In this study, the population number of banking employees would be 250 and the sample size of employees in the selected banking sector in Hang Tuah Jaya, Malacca is 152. The pilot test was successfully carried out with a sample size of 35 employees of the banking sector. The data from this study will be collected through the distribution of the questionnaire. To answer the research questions, the data will be analyzed with correlation and regression of Statistical Package for Social Science (SPSS Version 28).